Pemikiran Quraish Shihab Di Bidang Hukum Keluarga Islam Di Indonesia: Kajian Seputar Hukum Keluarga Islam Indonesia - Juliansyahzen, Muhammad Iqbal (Istinbath : Jurnal Hukum, 2021)
M. Quraish Shihab is one of the great Muslim scholars in Indonesia, who is very productive in his work and has great concern for the development of tafsir al-Quran. In addition, he is also known to have a concern for the development of Islamic law, including family law in Indonesia. The legal thought pattern is more rational-progressive by contextualizing the text in the dimensions of space, time, and culture. Among the results of his ijtihad which is quite a lot of discussion is about the hijab. The author also presents some other thoughts such as polygamy, sirri marriage, and nusyuz to see the thought pattern of M. Quraish Shihab. In the context of KHI as a reference to Islamic family law in Indonesia, he is not fully in agreement with the legal substance. The result of this research is Quraish tried to re-read the religious text in this case the source of Islamic law, namely the Qur'an and Hadith as well as the results of ijtihad scholars. The istislahi (based on mashlahat) became the foundation of the Quraish in responding to the development of family law practices. This method pays close attention to the side of human welfare in every provision of the Shari'ah that has been revealed. The principle of equality is also a concern of the Quraish in discussing the relationship between husband and wife.